An Analysis on Students’ Ability in Writing Expository - Annisa Ramadhani; Kisman Salija; Amra Ariyani (Journal of Excellence in English Language Education, 2022)
This study aims to determine students' ability to write expository text in the form of essays that focus on cause and effect based on five aspects of writing, namely content, organization, vocabulary, language use, and mechanics, at the Faculty of Language and Literature, specifically in the Business English class A semester of 2019. Eighteen (18) students did up the research sample. In this research, the descriptive qualitative approach was applied. To collect data, a writing test was conducted. According to the findings, students who wrote expository texts concentrating on cause and effect were able to write expository texts because the outcomes of their students' writing revealed that they were able to master five elements of writing which almost all students had the perfect vocabulary.